2015
DOI: 10.1299/mel.15-00367
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research and numerical simulation of moving molten metal pool

Abstract: Plenty of numerical simulations were performed to analyze the Molten Core-Concrete Interaction (MCCI) phenomena since 1980s. However, uncertainties remain among thermal hydraulic codes. Thus, in order to avoid the effect of uncertainties due to the different empirical formulas and interfacial models, a new CFD code based on Moving Particle Semi-implicit (MPS) method was proposed to simulate the MCCI event in the literature. Validation of the heat transfer and phase-change models is still necessary to utilize M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In this study, the heat transfer model and phase change model were introduced based on previous works [34][35][36][37][38][39][40]. Heat transfer calculations are essential to simulate melting-solidification behaviour.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the heat transfer model and phase change model were introduced based on previous works [34][35][36][37][38][39][40]. Heat transfer calculations are essential to simulate melting-solidification behaviour.…”
Section: Heat Transfer Modelmentioning
confidence: 99%
“…In this model, the viscosity was increased up to the immobilization solid fraction called the "critical solid fraction", and the viscosity was set as a constant value above the critical solid fraction to stop flowing. This empirical equation has been widely used to reproduce meltingsolidification behaviour [34][35][36][37][38][39][40]. However, it was suggested that the critical solid fraction for flowing is significantly affected by 1 the shear rate of the fluid, 2 the cooling ratio, and 3 the material characteristics [42,43].…”
Section: Phase Change Modelmentioning
confidence: 99%